Public theology, religious diversity, and interreligious learning: contributing to the common good through religious education - Pirner, Manfred L.; Lähnemann, Johannes; Haußmann, Werner; Schwarz, Susanne (Routledge research in religion and education, 2018)
Introduction -- Part A: public theology from diverse religious and non-religious perspectives -- Contributions of religions to the common good in pluralistic societies from a Christian perspective? : some critical remarks -- The contribution of religions to the common good in pluralistic societies : a Jewish perspective, exemplified by the concept of Tikkun Olam -- The contribution of religions to the common good in pluralistic societies : an Islamic perspective -- Islamic contributions to the universal conception of the common good in multi-confessional societies : hermeneutical foundations -- Towards enlightenment : Buddhism's contribution to common good through establishing contemplative culture -- The contributions of religions to the common good : philosophical perspectives -- Contributions of religions to the common good in a pluralistic society : an empirical answer from a sociological perspective -- Monotheism, curse or blessing? -- Part B. the challenge of interreligious dialogue and learning -- Public theology and interreligious dialogue -- Public theology or religious studies? : deliberations on the basis of multifaith religious education -- Public religious pedagogy and interreligious learning -- The public church and public religious education as forms of 'Protestant presence' : confessional and interreligious perspectives -- Islamic education in Europe : an opportunity for equal rights or a way to control Islam? -- The contribution of public religious education to promoting peace : perspectives from Israel -- The contribution of interreligious NGOs and interfaith initiatives to public education -- The spirituality of mindfulness: a religious contribution to public education